Case report: Squamous cell carcinoma and spindle cell sarcoma (SCS) arising in a mature cystic teratoma of the ovary - Qian, Xue-qian; Chen, Li-li; Zhu, Chang-kun; Chen, Ya-xia; Wan, Xiao-yun (Frontiers in Surgery, 2023)
Objective Malignant transformation of mature ovarian teratoma is a rare phenomenon, mainly occurring in postmenopausal period. Squamous cell carcinoma accounts for 80% of all malignant transformations. Sarcoma transformation is much less common and tends to imply a poorer prognosis and aggressiveness. Case report We report a case of undifferentiated sarcoma with squamous cell carcinoma in a mature cystic teratoma of the ovary in a 36-year-old woman. The tumor shows epithelial and stromal components. This is a unique report of a benign teratoma of the ovary with malignant transformation, showing epithelial and sarcomatous components. This young woman presented with abdominal distension and a rapidly enlarging ovario-derived pelvic mass with a slightly elevated CA199 tumor marker of 115.9U/mL. The woman underwent transabdominal excision of the left ovarian cyst on October 20, 2020. During the operation, rapid freezing pathological examination did not indicate malignancy. The postoperative paraffin pathology revealed undifferentiated sarcoma with squamous cell carcinoma (from mature cystic teratoma malignancy), and she finally received comprehensive staging surgery. Postoperative paraffin pathology showed no residual cancer in uterus and other tissues, and all lymph nodes were negative. The patient was finally diagnosed with ovarian malignant tumor IC1 stage (high-grade spindle cell sarcoma complicated with squamous cell carcinoma). Chemotherapy was completed three times after surgery, and no signs of recurrence were found after follow-up. Conclusion: The preoperative diagnosis and intraoperative rapid freezing examination of malignant transformation of mature teratoma of ovary are challenging.